5-HT1A Receptor Function Makes Wound Healing a Happier Process - Sadiq, Alia; Menchetti, Isabella; Shah, Ahmed; Jeschke, Marc G.; Belo, Cassandra; Carlos-Alcalde, Wendolyn; Hayat, Muhammad Qasim; Amini-Nik, Saeid (Frontiers in Pharmacology, 2018)
Skin wound healing is a multistage phenomenon that is regulated by cell-cell interplay and various factors. Endogenous serotonin is an important neurotransmitter and cytokine. Its interaction with the serotonin 1A receptor (5-HTR1A) delivers downstream cellular effects. The role of serotonin (5-hydroxytryptamine, 5-HT) and the 5-HT1A receptor has been established in the regeneration of tissues such as the liver and spinal motor neurons, prompting the investigation of the role of the 5-HT1A receptor in skin healing. This study assessed the role of the 5-HT1A receptor in excisional wound healing by employing an excisional punch biopsy model on 5-Ht1a receptor knockout mice. Post-harvest analysis revealed 5-Ht1a receptor knockout mice have impaired skin healing, accompanied by a greater number of F4/80 macrophages, which prolongs the inflammatory phase of wound healing. To further unravel this phenomenon, we employed the 5-HT1A receptor agonist [(R)-(+)-8-Hydroxy-DPAT hydrobromide] as a topical cream treatment in an excisional punch biopsy model. The 5-HT1A receptor agonist treated group showed a smaller wound area, scar size, and improved neovascularization, which contributed to improve healing outcomes as compared to the control. Collectively, these findings revealed that serotonin and 5-HT1A receptor play an important role during the healing process. These findings may open new lines of investigation for the potential treatment alternatives to improve skin healing with minimal scarring.